A study on the social status of indigenous women in Rangpur, Bangladesh - Mondol, Beauty; Paul, Basudev (International Multidisciplinary Research Journal, 2024)
Our society has not been able to break free from the subcontinent’s conservative patriarchy. There is a tendency to oppress women in society. For indigenous women, the situation is worse considering ethnicity, gender, religion, identity, and class. However, indigenous women in Bangladesh face numerous crises due to existing political, economic, and cultural barriers and inequalities. This study explored indigenous women’s social status in Bangladesh’s Rangpur region. This research followed the qualitative method to gather data in the field through FGD (Focus Group Discussions) and KID (Key Informant Interviews). The study’s findings show that lack of education, child marriage, prejudice, occupational oppression, insecurity, male superiority, the culture of forcing their decisions on women, and a lack of property rights are the most significant barriers to indigenous women’s growth in the Rangpur region. Furthermore, owing to the lack of adequate access to electricity, the internet, newspapers, and television in this region, they are deprived of the free flow of the media. As a result, women are unaware of various matters, such as government-allocated facilities, budget allocation, initiatives, work plans, and policies, making their challenges more visible. In the face of such multi-faceted problems in indigenous communities, the services and benefits of the government of Bangladesh, BRAC, Grameen Bank, CCDB, and World Vision are inadequate or absent in some areas; several NGOs, such as RDRS and Caritas, are just beginning. On the other hand, NGOs are more interested in microcredit practices than in developmental activities. The findings further show that the thinking and lifestyle of indigenous women of Rangpur region are improving through modernization. Many women from indigenous communities are now working as physicians, police officers, and teachers, while many are studying at colleges and universities.